THE INTERTEXTUALITY BETWEEN “HOPE” BY EMILY DICKINSON AND “CAGED BIRD” BY MAYA ANGELOU - Rosid Humam (JOSAR (Journal of Students Academic Research), 2022)
This research is classified as descriptive qualitative research. The researcher took the theme of literature appreciation which refers to one type of literature, namely poems. The writer compared two poems, namely Emily Dickinson's "Hope" and Maya Angelou's "Caged Bird". The purpose of the study was to determine the intertextuality of the two poems which were classified in the form of similar themes, contexts and circumstances. The results of this study indicate that there are similarities in the theme, context and circumstances contained in certain verses in the two poems.